ANALISIS KEMAMPUAN PENALARAN SISWA DALAM MENSKETSA GRAFIK TURUNAN : QUALITATIVE PERSPEKTIF - Besse Fika Aswari; Muhammad Ikram; Ahmad Bassar (UHAMKA Press, 2022)
The purpose of this qualitative research is to analyze students' reasoning in sketching derivative graphs. The instrument used in this study was a reasoning task sheet on the material for sketching derivative graphs that had been validated. The research subjects were class XII students of SMA Negeri I Batu Putih, totaling 17 students. The data collection procedure begins with students working on an instrument in the form of an assignment sheet accompanied by think-aloud to be able to determine students' reasoning abilities. Then conduct interviews with students to find out the reasoning abilities of students that are not visible when students work on the assignment sheet. then choose two subjects from the previous 17 prospective subjects where the selection of subjects is based on the data from the work on the assignment sheet, think-alound, and interviews. The two subjects were also selected based on the subject's ability to apply reasoning indicators when working on the assignment sheet. There are 4 reasoning indicators, namely identifying problems, analyzing problems, building connections (relationships between concepts), and sketching graphs.